Detection of photos from the same event captured by distinct cameras - Figueirêdo, Hugo Feitosa de; Silva, João Paulo Ribeiro da; Leite, Daniel Farias Batista; Baptista, Cláudio de Souza (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Currently one of the main features of events such as birthday party, wedding, conferences, and trips is the amount of photos taken from different digital cameras. The plethora of photo devices such as smartphones and tablets have contributed for this avalanche of photos. Social networks such as Facebook, Orkut, Flickr, and Picasa store a large volume of photos. As a consequence, the retrieval of such photos demands new systems. The automatic annotation of photo context metadata such as timestamp, and geographic coordinates, represents a challenge. In this paper, we propose a method for automatic event detection based on photos taken from different cameras in a same event. The proposed method aims to improve the retrieval of photos in a same event, to make cross tagging and to detect errors in the annotations.